Analisis Efektivitas Penggabungan Metode Transformasi Wavelet-GR4J Guna Pengalihragaman Hujan Debit (Studi Kasus : DAS Siak Hulu) - Zaky Ilhami; Manyuk Fauzi; Imam Suprayogi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This research studies the rainfall-runoff modeling using variations of the model by forming joint models (hybrid model) of the Wavelet Transformation and GR4J (Génie Rural à 4 parametres Journalier) on Watershed (DAS) Siak Hulu. Combined method of Wavelet-GR4J transformation expected can increase Nash -Sutcliffe Coefficient and Correlation Coefficient. This GR4J model use input data including daily rainfall data on new Petapahan station and daily potential evapotranspiration data which is the result of the CropWat program with climatology input data on Kampar market station. The modeling result is tested using daily observation debit data in Pantai Cermin station. This modeling optimized four free parameters such as Maximum Capacity Production Store (X1) with a value of 440.31 mm, Groundwater Changes Coefficient (X2) with a value of 2.92 mm, Maximum Capacity (X3) with a value of 20mm, and the Hydrograph Unit Ordinate’s Peak Time (X4) with a value of 26.57 days. At a later stage, in particular calibration and verification in the year thereafter. Simulation of Wavelet-GR4J Transformation resulted value equation Nash-Sutcliffe Coefficient of 49.255% and the Correlation Coefficient (R) of 0,762. Combining process of Wavelet-GR4J Transformation method produces a better model performance of the model GR4J based on the Nash-Sutcliffe Coefficient and Correlation Coefficient.Keywords: wavelet transformation, GR4J, calibration, verification, simulation.